1997
DOI: 10.1021/jp962994e
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns and Nonclassical Kinetics of Competing Elementary Reactions:  Chromium Complex Formation with Xylenol Orange in a Capillary

Abstract: An experimental investigation of chemical reaction fronts, created by an initial separation of reactants, is reported for a system of two competing reactions. Spatiotemporal patterns are observed experimentally for the competing reaction front and are accounted for quantitatively by a reaction-diffusion model. We use the reaction of xylenol orange with Cr3+ in aqueous solution. Different oligomers of Cr3+ provide the two kinetically different species that react competitively with xylenol orange. The parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…as t → ∞, with |η| < ∞ fixed (38) and by matching we conclude A ′ (∞) = A 1 , where A 1 (ν) ≡ A ′ (0)/2 can be expressed in terms of ν(q) using Eq. (27). In light of Eq.…”
Section: Asymptotic Matchingmentioning
confidence: 98%
See 1 more Smart Citation
“…as t → ∞, with |η| < ∞ fixed (38) and by matching we conclude A ′ (∞) = A 1 , where A 1 (ν) ≡ A ′ (0)/2 can be expressed in terms of ν(q) using Eq. (27). In light of Eq.…”
Section: Asymptotic Matchingmentioning
confidence: 98%
“…Reaction−diffusion processes have been the subject of intense and continuous interest since the work of Smoluchowski. A crucial feature of many such processes controlling pattern formation and reaction efficiency is the “reaction front”, a dynamic but localized region where reactions are most actively occurring and which separates regions rich in the individual reactants. The simplest theoretical model of a reaction front, introduced more than a decade ago by Gálfi and Rácz, is the “mean-field” model for two initially separated species A and B reacting to produce an inert species C. Since then, the case of two diffusing reactants A and B has been thoroughly studied analytically and numerically, and some predictions of the mean-field model have been checked in the experiments. …”
Section: Introductionmentioning
confidence: 99%
“…The authors explained the observed splitting of the reaction zone as an effect of the immobile component. Taitelbaum et al [4] and Yen et al [5] theoretically and experimentally studied the competing reactions of Cr 3+ ions with xylenol orange and the corresponding pH dependences of the distribution of the reaction product. Reaction front splitting and temporary nonmonotonic behavior of the global reaction rate was observed.…”
Section: Introductionmentioning
confidence: 99%